Green business: legal mechanisms of incentivization ("Journal "U". Economy. Management. Finance.", 2025)
The study examines the legal mechanisms of stimulating «green business» by forming certain national projects on the territory of the Russian Federation, establishing as a priority direction the application of ESG approach to business.
Keywords: green business; ESG-project; national projects; incentives